1991
DOI: 10.1007/bf00172139
|View full text |Cite
|
Sign up to set email alerts
|

Competitive regimes and female bonding in two species of squirrel monkeys (Saimiri oerstedi and S. sciureus)

Abstract: Ecological and behavioral data from longterm field studies of known individuals in two closely related squirrel monkey species (Saimiri oerstedi and S. seiureus) were used to examine hypotheses about the source of variation in female bonding among groupliving primates. Social relationships in species which live in cohesive groups are thought to depend on the nature of competition for resources. S. oerstedi and S. sciureus both live in large groups and are subject to intense predation. Direct feeding competitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(112 citation statements)
references
References 31 publications
7
100
1
4
Order By: Relevance
“…The Peruvian common squirrel monkey (Saimiri sciureus) is RN, while the Costa Rican red-backed squirrel monkey (S. oerstedi) is DE (Mitchell et al 1991;Boinski and Mitchell 1994). The two species have similar group sizes and diets, and face similar predation risk.…”
Section: Comparative Testsmentioning
confidence: 99%
“…The Peruvian common squirrel monkey (Saimiri sciureus) is RN, while the Costa Rican red-backed squirrel monkey (S. oerstedi) is DE (Mitchell et al 1991;Boinski and Mitchell 1994). The two species have similar group sizes and diets, and face similar predation risk.…”
Section: Comparative Testsmentioning
confidence: 99%
“…Detailed accounts of coalitions over food resources are spotty (e.g., Janson, 1985;Mitchell et al, 1991;Perry, 1997;Hirsch, 2007;Vogel et al, 2007) and the empirical literature seems to be silent about their benefits or the division of rewards among the coalition members. This may reflect the fact that coalitions in a feeding context are rare, or researchers rarely report coalitions in this context.…”
Section: Increasing Access To Food Resourcesmentioning
confidence: 99%
“…Yet, in some species an important proportion of conflicts over food are polyadic. For example, up to 22.8% of all resource-based conflicts in squirrel monkeys (Saimiri sciureus, Mitchell et al, 1991) are polyadic, and 25% of female-female coalitions against males in capuchin monkeys (C. capucinus) originate in the context of feeding competition between a male and a female (Perry, 1997; see also Vogel et al, 2007). Outside the primates, one study reported that coalitions failed to increase immediate access to food at carcasses in female hyenas (Smith et al, 2010).…”
Section: Increasing Access To Food Resourcesmentioning
confidence: 99%
“…Instead, comparative approaches have used primarily captive or provisioned populations [87,88] or included only a few wild, unprovisioned populations or species [96][97][98]. To date, only two broader comparisons have been conducted with wild, unprovisioned primates [91,99], and both studies were restricted to agonistic behaviour.…”
Section: (B) the Roads Less Travelledmentioning
confidence: 99%